A Rare Case of Isolated Right Ventricular Non-compaction With the Novel TTN Mutation - Huang, Piao-piao; Tang, Ya-xin; Huang, Xian-sheng (Frontiers in Cardiovascular Medicine, 2022)
Isolated right ventricular noncompaction cardiomyopathy (RVNC) is rare yet life-threatening if left untreated, especially when accompanied by ventricular tachycardia (VT). We describe a rare case of isolated RVNC, presenting as prominent and excessive trabeculation of the right ventricle (RV), with an abnormal electrocardiogram (ECG). The transthoracic echocardiography (TTE), Computed Tomography Angiography (CTA) and ventricular angiography results clearly demonstrated an isolated spongy RV, both anatomically and functionally. Genetic testing identified missense mutation of TTN. Combined, the diagnosis of RVNC was established. The subsequent combination of heart failure therapy, antiarrhythmic and anticoagulation therapy was effective with a favorable outcome. This case report describes the possible etiology, manifestation, characteristic images, and problematic diagnostic criteria of the isolated RVNC. This case also emphasizes the necessity of comprehensive cardiac screening in familial cardiomyopathy.